Studies on Crop Weather Relationships in Mustard - Rao, V Umamaheshwara; Singh, Diwan; Pal, Som; Bishnoi, O P (Annals of Arid Zone, 2016)
An experiment was conducted at CCS Haryana Agricultural University. Hisar research farm. during robi 1993-94 and 1994-95 to study energy balance and to identify important weather parameters intluencing dry matter production in three mustard varieties. viz . RH-30, Varuna and .Laxmi. Latent heat of vaporization (LE) varied with growth stage owing to variation in leaf area index (LAI). Maximum LE values were observed when crop attained maximum LAI. Sensible heat nux (A) kept on increasing till maturity of crop. Diurnal trends for components of energy balance indicated that net radiation (Rn), LE and A were highest during noon hours. The diurnal changes in soil heat flux (G) were very small. Around 80% of the dry matter variation can be explained by weather parameters. Temperature was most important that explained dry matter variation at acceptable levels.